Combination of Electrochemical Processes with Membrane Bioreactors for Wastewater Treatment and Fouling Control: A Review - Ensano, Benny M. B.; Borea, Laura; Naddeo, Vincenzo; Belgiorno, Vincenzo; de Luna, Mark D. G.; Ballesteros, Florencio C. (Frontiers in Environmental Science, 2016)
This paper provides a critical review about the integration of electrochemical processes into membrane bioreactors (MBR) in order to understand the influence of these processes on wastewater treatment performance and membrane fouling control. The integration can be realized either in an internal or an external configuration. Electrically enhanced membrane bioreactors or electro membrane bioreactors (eMBRs) combine biodegradation, electrochemical and membrane filtration processes into one system providing higher effluent quality as compared to conventional MBRs and activated sludge plants. Furthermore, electrochemical processes, such as electrocoagulation, electrophoresis, and electroosmosis, help to mitigate deposition of foulants into the membrane and enhance sludge dewaterability by controlling the morphological properties and mobility of the colloidal particles and bulk liquid. Intermittent application of minute electric field has proven to reduce energy consumption and operational cost as well as minimize the negative effect of direct current field on microbial activity which are some of the main concerns in eMBR technology. The present review discusses important design considerations of eMBR, its advantages as well as its applications to different types of wastewater. It also presents several challenges that need to be addressed for future development of this hybrid technology which include treatment of high strength industrial wastewater and removal of emerging contaminants, optimization study, cost benefit analysis and the possible combination with microbial electrolysis cell for biohydrogen production.